Soil Stabilization Using Crumb Rubber Powder (International Journal of Innovative Research in Computer Science & Technology, 2022)
Because there are more used car tyres  produced each year, disposing of them has become a  significant environmental issue on a global scale. Utilizing  used tyres will reduce the effect on the environment and  increase resource preservation. The stabilisation of soils  using CRP (5%, 10%, 15%) is discussed in this article. The  conduct and effectiveness of the stabilised soil were  evaluated using the soil properties, compaction, California  bearing ratio (CBR), and direct shear test. When soil and  CRP are combined, it is seen that the maximum dry density  and ideal moisture content decline as the percentage of  crumb rubber in the soil increases. Bearing capacity and  tensile strength are barely affected by blending.  Nevertheless, the numbers stayed within reasonable bounds.
Keywords: Plastic Strips; Stabilizer; Stabilization